GHIP in Streptococcus pneumoniae is involved in antibacterial resistance and elicits a strong innate immune response through TLR2 and JNK/p38MAPK. (15th August 2014) - Dong, Jie; Wang, Jian; He, Yujuan; Li, Chenwei; Zhou, Aie; Cui, Jin; Xu, Wenchun; Zhong, Liang; Yin, Yibing; Zhang, Xuemei; Wang, Hong
<x xml:space="preserve">Abstract</x> Interaction between pneumococcal virulence factors and innate immune receptors triggers host responses via specific signaling pathways after infection. By generating a deficient mutant, we show here that, compared with the wild‐type parent strain, glycosyl hydrolase 25 relating to invasion protein (GHIP) mutant strain was impaired in rapid dissemination into vessels and caused less severe inflammation in mice lungs. Further study demonstrated that the lack of this protein in Streptococcus pneumoniae caused an increased susceptibility to whole blood or neutrophils, while this impairment could be recovered by supplementing recombinant GHIP (rGHIP). Additionally, secreted GHIP could be detected in culture medium, and purified protein was able to induce the release of tumor necrosis factor α and interleukin 6 from peritoneal macrophages. Further investigations revealed that the induction of interleukin 6 by this virulence factor depended on the phosphorylation of c‐Jun N‐terminal kinase and p38 mitogen activated protein kinase and Toll‐like receptor 2. Taken together, GHIP, a novel pneumococcal virulence factor, appeared to play a critical role in bacterial survival and the induction of host innate immune response during pneumococcal infection.